(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article analyses the representation of agricultural terms in lexicographic systems in different languages, their structure, translation and structural features. It also considers modern approaches to compiling specialised dictionaries, the possibilities of selecting and organising terms based on corpus linguistics, and their use in an interdisciplinary context.